Transcriptomic and Metabolomics Profiling of Phage–Host Interactions between Phage PaP1 and Pseudomonas aeruginosa - Zhao, Xia; Shen, Mengyu; Jiang, Xingyu; Shen, Wei; Zhong, Qiu; Yang, Yuhui; Tan, Yinling; Agnello, Melissa; He, Xuesong; Hu, Fuquan; Le, Shuai (Frontiers in Microbiology, 2017)
The basic biology of bacteriophage–host interactions has attracted increasing attention due to a renewed interest in the therapeutic potential of bacteriophages. In addition, knowledge of the host pathways inhibited by phage may provide clues to novel drug targets. However, the effect of phage on bacterial gene expression and metabolism is still poorly understood. In this study, we tracked phage–host interactions by combining transcriptomic and metabolomic analyses in Pseudomonas aeruginosa infected with a lytic bacteriophage, PaP1. Compared with the uninfected host, 7.1% (399/5655) of the genes of the phage-infected host were differentially expressed (DEGs); of those, 354 DEGs were downregulated at the late infection phase. Many of the downregulated DEGs were found in amino acid and energy metabolism pathways. Using metabolomics approach, we then analyzed the changes in metabolite levels in the PaP1-infected host compared to un-infected controls. Thymidine was significantly increased in the host after PaP1 infection, results that were further supported by increased expression of a PaP1-encoded thymidylate synthase gene. Furthermore, the intracellular betaine concentration was drastically reduced, whereas choline increased, presumably due to downregulation of the choline–glycine betaine pathway. Interestingly, the choline–glycine betaine pathway is a potential antimicrobial target; previous studies have shown that betB inhibition results in the depletion of betaine and the accumulation of betaine aldehyde, the combination of which is toxic to P. aeruginosa. These results present a detailed description of an example of phage-directed metabolism in P. aeruginosa. Both phage-encoded auxiliary metabolic genes and phage-directed host gene expression may contribute to the metabolic changes observed in the host.